2017
DOI: 10.1364/ol.42.002427
|View full text |Cite
|
Sign up to set email alerts
|

CW-to-pulse conversion using temporal Talbot array illuminators

Abstract: We report on the linear conversion of continuous-wave (CW) laser light to optical pulses using temporal Talbot array illuminators (TAIs) with fractional orders 1/q(q≤10), implemented by use of multilevel PM and dispersive propagation in a chirped fiber Bragg grating. The generated, sub-nanosecond optical pulse trains have repetition rates in the gigahertz range and show the presence of satellite pulses originated by the finite electrical modulation bandwidth (7.5 GHz). Though this fact impacts the resulting ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 18 publications
0
29
0
Order By: Relevance
“…For instance, a highbandwidth intensity modulator can carve pulses out of a continuous-wave (CW) beam by attenuating the beam in a desired pulse sequence. Techniques with greater efficiency (up to unity in some cases) have been demonstrated using rapid amplitude or phase modulation schemes based on time-lenses [74][75][76], temporal zone plates [77], temporal holograms [78,79], or the temporal Talbot effect [80], followed by a dispersive delay line that compresses the modulated beam into a pulse train. The improved efficiency can reduce the number of amplification stages needed; however, these techniques generate a repetitive pulse train, rather than individual pulses, and are therefore less versatile than techniques such as direct intensity modulation.…”
Section: Generating Pulses Without Mode-lockingmentioning
confidence: 99%
“…For instance, a highbandwidth intensity modulator can carve pulses out of a continuous-wave (CW) beam by attenuating the beam in a desired pulse sequence. Techniques with greater efficiency (up to unity in some cases) have been demonstrated using rapid amplitude or phase modulation schemes based on time-lenses [74][75][76], temporal zone plates [77], temporal holograms [78,79], or the temporal Talbot effect [80], followed by a dispersive delay line that compresses the modulated beam into a pulse train. The improved efficiency can reduce the number of amplification stages needed; however, these techniques generate a repetitive pulse train, rather than individual pulses, and are therefore less versatile than techniques such as direct intensity modulation.…”
Section: Generating Pulses Without Mode-lockingmentioning
confidence: 99%
“…Results can then be normalized by the Talbot length z T defined as: zT=1π0.5em||β20.5emΔf2, where Δf is the frequency spacing between two non‐zero spectral components ( Δf = 2 f 0 in our ideal case). After a propagation distance of z T /4, the phase modulation is converted into a binary intensity modulation (red curve, Figure 3(B)), typical of a Talbot array illuminator 25‐27 . After z T /2, a continuous wave is reconstructed as expected from the self‐imaging process.…”
Section: Ideal Binary Phase Modulationmentioning
confidence: 99%
“…1) Temporal phase sequences, 2) optical spectra of the obtained pulse trains, 3) instantaneous power traces of the obtained pulse trains. Reproduced with permission . Copyright 2017, Optical Society of America.…”
Section: Review Of Experimental Work On Energy‐preserving Signal Procmentioning
confidence: 99%
“…[123,124] Finally, it is worth mentioning that Talbot-based methods have also been used for energy-preserving manipulation of continuous-wave (CW) signals. R. Fernández-Pousa et al demonstrated efficient CW-to-pulse conversion through a methodology based on the reviewed energy redistribution methods [125] (experimental examples shown in Figure 21). This can be interpreted as the time-domain counterpart of the Talbot array illuminator (TAI), a process by which a plane wave is focused into a set of localized bright spots through the interplay of a spatial phase mask and free-space propagation.…”
Section: Additional Properties and Extended Functionalitymentioning
confidence: 99%
See 1 more Smart Citation